Aeromonas spp. Prevalence, virulence, and antimicrobial resistance in an ex situ program for tThreatened freshwater fish—A pilot study with protective measures - Grilo, Miguel (2022)
Ex situ breeding programs are important conservation tools for endangered freshwater fish. However, developing husbandry techniques that decrease the likelihood of disease, antimicrobial resistance, and virulence determinants acquisition during this process is challenging. In this pilot study, we conducted a captivity experiment with Portuguese nase (Iberochondrostoma lusitanicum), a critically endangered leuciscid species, to investigate the influence of simple protective measures (i.e., material disinfection protocols and animal handling with gloves) on the dynamics of a potential pathogenic genus, Aeromonas, as well as its virulence profiles and antimicrobial resistance signatures. Our findings show that antimicrobial resistance in Aeromonas spp. collected from I. lusitanicum significantly increased during the extent of the assay (5 weeks), with all isolates collected at the end of the study classified as multidrug-resistant. Additionally, humans handling fishes without protective measures were colonized by Aeromonas spp. The use of protective measures suggested a decreasing trend in Aeromonas spp. prevalence in I. lusitanicum, while bacterial isolates displayed significantly lower virulence index values when virulence phenotypical expression was tested at 22 °C. Despite this study representing an initial trial, which needs support from further research, protective measures tested are considered a simple tool to be applied in ex situ breeding programs for aquatic animals worldwide. Furthermore, current results raise concern regarding antimicrobial resistance amplification and zoonotic transmission of Aeromonas spp. in aquatic ex situ programs.